Pendeteksi Bahasa Isyarat menjadi Suara Berbasis Artificial Intelligence Metode Blazepose (PEBISI) dengan Output Suara dan Text - Nurkholiq Fahrurozi, Riziq; Saragih, Yuliarman (Aisyah Journal Of Informatics and Electrical Engineering (A.J.I.E.E), 2024)
This research introduces the Sign Language to Voice Converter based on Artificial Intelligence using the Blazepose method (PEBISI) for accurate translation of sign language into voice and text. The main objective of this study is to develop a system that can accurately translate sign language into voice and text. In the PEBISI method, the movements of the user's hands and body are detected and analyzed using Blazepose technology, while an AI model is trained to interpret these movements and generate corresponding voice and text output. Through implementation and evaluation using sign language datasets, PEBISI demonstrates excellent performance in recognizing hand movements and producing accurate voice and text translations. The test results also reveal the reliability of the system and the potential for further development to enhance the quality of sign language translation. Therefore, this research contributes to the development of more inclusive technology, facilitating communication between sign language users and individuals who do not understand sign language.